2016
DOI: 10.1055/s-0035-1558089
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Diterpenes as Putative Marker Compounds Distinguishing Agnus Castus Fruit (Chaste Tree) from Shrub Chaste Tree Fruit (Viticis Fructus)

Abstract: Agnus Castus Fruit is defined in the European Pharmacopoeia as the dried ripe fruit of Vitex agnus-castus. In Europe it is used as a medicine targeting premenstrual syndrome and climacteric disorder. In Japan, Agnus Castus Fruit is becoming popular as a raw material for over-the-counter drugs and health food products, though its congenic species, Vitex rotundifolia and Vitex trifolia, have been used as Shrub Chaste Tree Fruit in traditional medicines. Therefore, it is important to discriminate these Vitex plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The original plant species of SCTF and ACF crude drugs were previously identified based on their DNA sequences. 8) General Procedures For column chromatography, Silica gel N60 (Kanto Chemical, Tokyo, Japan), YMC GEL ODS-A S-150 (YMC, Kyoto, Japan), and MCI GEL CHP-20 (Mitsubishi Chemical, Tokyo, Japan) were used as chromatographic carriers. The preparative HPLC system was composed of a JASCO PU-2089 Plus, JASCO MD-2010 Plus, and JASCO CO-2060 Plus equipped with a COSMOSIL 5C 18 -MS-II (20 mm i.d.×250 mm; Nacalai Tesque, Kyoto, Japan), COSMOSIL πNAP (10 mm i.d.×250 mm, Nacalai Tesque), or Shodex GF310HQ (4.6 mm i.d.×250 mm; Showa Denko, Kawasaki, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The original plant species of SCTF and ACF crude drugs were previously identified based on their DNA sequences. 8) General Procedures For column chromatography, Silica gel N60 (Kanto Chemical, Tokyo, Japan), YMC GEL ODS-A S-150 (YMC, Kyoto, Japan), and MCI GEL CHP-20 (Mitsubishi Chemical, Tokyo, Japan) were used as chromatographic carriers. The preparative HPLC system was composed of a JASCO PU-2089 Plus, JASCO MD-2010 Plus, and JASCO CO-2060 Plus equipped with a COSMOSIL 5C 18 -MS-II (20 mm i.d.×250 mm; Nacalai Tesque, Kyoto, Japan), COSMOSIL πNAP (10 mm i.d.×250 mm, Nacalai Tesque), or Shodex GF310HQ (4.6 mm i.d.×250 mm; Showa Denko, Kawasaki, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In China, VTF has been used as a traditional Chinese medicine (TCM) for the treatment of cold and various pain symptoms such as headache, migraine, toothache, and rheumatism for more than a 1000 years (Park et al, 2014; Rani & Sharma, 2013). In Japan, VTF has been taken as a natural analgesic (Oshima et al, 2016). Moreover, recent research has indicated the extensive biological activities of VTF including antitumor (Cao et al, 2016; Haïdara, Zamir, Shi, & Batist, 2006; Kobayakawa, Satonishimori, Moriyasu, & Matsukawa, 2004), antinociceptive, antihyperprolactinemia (Hu et al, 2007), antifibrosis (Zhou et al, 2017), antiinflammation (Bao et al, 2018; Lee, Jung, Ji, & Bae, 2017), antiasthma (Park et al, 2014) as well as the rosiglitazone‐like effects (Nishina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the micrographic images obtained from previous research were fuzzily hand‐painted with strong subjectivity. Besides, a highly accurate approach with DNA bar coding was set up (Oshima et al, 2016), while the high cost and the complicated experimental protocol make it limited for authentication of VTF.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, VF derived from the fruit of Vitex rotundifolia or Vitex trifolia , used for sedation, relieving pains and diminishing inflammation. Moreover, its congenic species, Vitex agnus-castus , was used as a medicine for curing climacteric disorder and premenstrual syndrome in Europe [6].…”
Section: Introductionmentioning
confidence: 99%